PENGEMBANGAN SISTEM PENGELOLAAN KEUANGAN KEPEGAWAIAN UNIVERSITAS ATMA JAYA MAKASSAR - Carolus, Ridnaldy Yunior (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2019)
The main goal of this thesis is to develop formerly made into one systems and integrating with a financial system UAJM to be a system that can support the process financial management and employment can help improve performance in personalia to managing personnel at the University of Atma Jaya Makassar.Keywords: Management, Personalia, The Financial System, University.